Participatory approaches for systems intensification - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Approach implemented by the African Highlands Initiative in its technology adoption program. It features the inclusion of farmers in AHI’s research processes. It also adopts a team-based, multidisciplinary approach toward solving locally identified problems.